Writing Anxiety in Relation to High Performing Students’ English Compositions - Kurniasih Kurniasih (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2018)
This study attempts to investigate the correlation between writing anxiety and writing performance. Writing is a productive skill in which English learners are required to master it well because they will have to write many English compositions during their study. Out of fifty students who registered in Writing II course only nineteen students participated in this study because their writing score is ≥ 80.  The data was analyzed by using SPPS version 17.0 to find the correlation between writing anxiety and writing performance. The results of this study show r is -587 and significant at the level 0.05.  It means that there was significant correlation between students’ writing anxiety and writing performance; therefore the alternative hypothesis is accepted.  Furthermore, it reveals that writing anxiety was negatively correlated with students’ writing performance. In other words, when students felt anxious, they tend to produce poor compositions. In contrast, when their anxiety is low, they will likely to produce good piece of writing.